Risk of hepatitis B occurrence in pregnant women in Kulon Progo Regency, 2017-2018 - Nurjanna; Kusnanto, Hari (BKM Public Health and Community Medicine, 2021)
Purpose: This study aimed to identify risk factors related to the incidence of hepatitis B among pregnant women in Kulon Progo District. Methods: This study used a case-control design with a ratio of 1: 1. The sample size was 132 respondents with 66 cases and 66 controls. Data collected through interviews with mothers was recorded in the hepatitis B screening surveillance report of pregnant women in Kulon Progo District 2017 to 2018. The data were analyzed using Fisher’s exact test, chi-square test, and multiple logistic regression. Results: The results showed that the average age of respondents was 30.75±6.07, 71.2% were housewives and 64.4% had high school education. Bivariate analysis showed that age, parity, history of miscarriage, surgical history, family history of hepatitis and shared personal hygiene items had relationships with the incidence of hepatitis B. The results of multivariate analysis in the final model showed parity (OR=4.41) and family history of hepatitis (OR = 20.23) as significant risk factors for the incidence of Hepatitis B among pregnant women. Conclusion: High parity and a family history of hepatitis were found to increase the risk of hepatitis B among pregnant women. Efforts to prevent household transmission of hepatitis B should include increasing knowledge through education and counseling, as well as screening family members or other individuals living in the same household as mothers with hepatitis B.